Risk and Surveillance of Cancers in Primary Biliary Tract Disease - Valery Hrad; Yoftahe Abebe; Syed Haris Ali; Jared Velgersdyk; Mohammed Al Hallak; Mohamad Imam (Gastroenterology Research and Practice)
Primary biliary diseases have been associated in several studies with various malignancies. Understanding the risk and optimizing surveillance strategy of these malignancies in this specific subset of patients are an important facet of clinical care. For instance, primary sclerosing cholangitis is associated with an increased risk for cholangiocarcinoma (which is very challenging to diagnose) and when IBD is present for colorectal cancer. On the other hand, primary biliary cirrhosis patients with cirrhosis or not responding to 12 months of ursodeoxycholic acid therapy are at increased risk of hepatocellular carcinoma. In this review we will discuss in detail the risks and optimal surveillance strategies for patients with primary biliary diseases.